2023
DOI: 10.1007/s40279-023-01821-4
|View full text |Cite
|
Sign up to set email alerts
|

Short High-Intensity Interval Exercise for Workplace-Based Physical Activity Interventions: A Systematic Review on Feasibility and Effectiveness

Abstract: Background Workplace exercise interventions showed good results, but lack of time was often reported as a barrier to participation. To overcome this problem, several studies attempted to implement short high-intensity interval training (HIT) within the workplace. Objectives The aim of this systematic review is to explore the feasibility and effectiveness of HIT interventions within the workplace setting. Data sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Another study emphasized the importance of a nature prescription, which includes regular physical activity, in improving human health including blood pressure, depression, and anxiety [ 7 ]. An intervention in exercise-related activities improves the health of employees [ 8 ]. Studies suggested that individuals of low socio-economic upbringing are less likely to engage in physical activity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study emphasized the importance of a nature prescription, which includes regular physical activity, in improving human health including blood pressure, depression, and anxiety [ 7 ]. An intervention in exercise-related activities improves the health of employees [ 8 ]. Studies suggested that individuals of low socio-economic upbringing are less likely to engage in physical activity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the substantial amount of time individuals spend at their workplaces, this context has been proposed as a suitable environment for implementing interventions aimed at fostering workers’ health through lifestyle modifications. Various types of physical activities (stretching, strength training, aerobic exercises, high-intensity interval training, or various combinations thereof) have been proposed, yielding promising but occasionally divergent outcomes ( 4 , 19 , 20 , 36 , 37 ). Well-designed, randomized, and controlled studies remain essential to explore the impact of PA on workers’ physical and mental well-being.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many studies investigated the effects of PA practice (both conducted in and out the workplace setting) on workers’ physical and mental health, showing that PA could be effective in reducing MSDs ( 4 , 17 ) and mental health problems ( 17 , 18 ), improving physical fitness ( 19 , 20 ) and likely - indirectly - work performance ( 21 ). However, to the authors’ knowledge, the mutual interactions among PA, physical and mental health, and workplace well-being have been less studied.…”
Section: Introductionmentioning
confidence: 99%
“…Six reviews pursued the objective of identifying solely the effectiveness of PA interventions on promoting PA and/or reducing sedentary behavior (39, 41-43, 45, 54). Two reviews focused on the effects of PA interventions on improving psychological well-being and mental health (37,38,50,52) and two assessed workability (46,53). One review each showed a fitness approach (40,49) or focused musculoskeletal pain (48).…”
Section: Main Objectives Of the Reviewsmentioning
confidence: 99%
“…One review each showed a fitness approach (40,49) or focused musculoskeletal pain (48). Five reviews showed a combined approach regarding the objectives, considering physical activity behavior and health outcomes (38,40,44,47,52). The outcomes of the respective primary studies could be assigned to the following categories: physical activity-related outcomes (38, 39, 41-45, 47, 52, 54), health-related outcomes (37,38,40,44,(47)(48)(49)(50)52), and job-related outcomes (38,41,46,48,52,53).…”
Section: Main Objectives Of the Reviewsmentioning
confidence: 99%